An Efficient Track-Scale Model for Laser Powder Bed Fusion Additive Manufacturing: Part 2—Mechanical Model - Tangestani, Reza; Sabiston, Trevor; Chakraborty, Apratim; Yuan, Lang; Krutz, Nicholas; Martin, Étienne (Frontiers in Materials, 2021)
This is the second of two manuscripts that presents a computationally efficient full-field deterministic model for laser powder bed fusion (LPBF). The Hybrid Line (HL) thermal model developed in part I is extended to predict the in-process residual stresses due to laser processing of a nickel-based superalloy, RENÉ 65. The computational efficiency and accuracy of the HL thermo-mechanical model is first compared to the exponential decaying heat input model on a single-track simulation. LPBF thin-wall builds with three different laser powers and four printing patterns are evaluated in this study and compared with part-scale simulations. The simulations show good agreements with the experimental X-Ray diffraction measured residual stresses. Compared to the laser power, the scanning pattern is demonstrated to have significant effects on residual stresses. Laser scan patterns utilizing short laser paths generate lower tensile stress along the longitudinal direction of the part and higher compressive stress along the build direction.